DIGITALIZATION INFLUENCE ON THE ESTIMATION WORK EFFICIENCY OF THE DEVELOPMENT BANKS (ON THE EXAMPLE OF THE ASIAN DEVELOPMENT BANK) - S. Matveevskii (Вестник университета, 2018)
The article reveals the possibilities of digitalization in evaluating the effec-tiveness of a development bank. The conditions for the successful operation of the de-velopment bank, the circumstances that adversely affect these banks have generalized. The experience of the Asian Development Bank in using a multi-level system for eval-uating the effectiveness of its activities, based on a set of indicators and indicators has analysed. The author proposes to use such elements of digitalization as big data and their analysis, project models, artificial intelligence in evaluating the effectiveness of the work of the development bank. The results of Vnesheconombank’s activities al-low us to recommend it to use the experience of the Asian Development Bank, related to the evaluation of its activities.